Short Communication: Inventory of traditional medicinal plants and their uses from Atinggola, North Gorontalo District, Gorontalo Province, Indonesia - NOVRI YOULA KANDOWANGKO; MUKHLISULFATIH LATIEF; RAMPI YUSUF (Biodiversitas Journal of Biological Diversity, 2018)
Kandowangko NY, Latief M, Yusuf R. 2018. Inventory of traditional medicinal plants and their uses from Atinggola, North Gorontalo District, Gorontalo Province, Indonesia. Biodiversitas 19: 2294-2301. Medicinal plants have been used by the people of Gorontalo as a hereditary tradition. But this knowledge has not spread to the wider community because the traditional wisdom about medicinal plants has not been documented, stored and managed properly by employing digital tools. The purpose of this study is to prepare an inventory of the traditional medicinal plants and the details of their uses in Atinggola, North Gorontalo district, Indonesia. Data has been collected by ethnobotanical survey method and analyzed using the descriptive qualitative method. The study has shown that 38 species of medicinal plants, belonging to 20 families, are used to cure many diseases by the traditional healers of Atinggola. Among them, 6 species are used to treat fever, 5 species to treat skin diseases, 2 species each to treat cancer, gastrointestinal diseases, liver diseases, and as body tonic to restore power; 1 species each to treat toothache, malaria, tonsillitis, allergies, eye irritation, wound infections and tuberculosis (TBC). Plant parts used in the treatment practices are leaf, fruit, flower, rhizome, root, stem, seed, shoots, midribs parts, etc. However, the most dominant part used is the leaf of the plants. Various methods such as boiling, squeezing, scraping, chewing, smashing, brewing, etc. are used to prepare the medicines. 29 species (76.31%) of medicinal plants are collected from cultivated sources such as backyards and gardens while 9 species (23.68%) are still sourced from forests.